Tesla motors: disrupting the automotive industry - Braunfels, Niklas Sven Johannes (2022)
This Work Project presents a case study about Tesla and how it disrupted the automotive industry. It concludes, that Tesla disrupted the automotive industry by challenging the predominant internal combustion engine vehicles with the commercialization of innovative electric vehicles and its infrastructure. It therefore applied several disruptive strategies. The paper is structured as follows: Firstly, a case study on Tesla is presented. Secondly, a literature review and taxonomy of disruptive innovation are introduced and applied to the case study. Finally, to conclude, Tesla ́s distinctive capabilities and future challenges will be discussed.